Multi-Poisson process analysis of real-time soft-error rate measurements in bulk 65 nm and 40 nm SRAMs. (September 2017) - Moindjie, S.; Autran, J.L.; Munteanu, D.; Gasiot, G.; Roche, P.
Abstract: Altitude and underground real-time soft error rate (SER) measurements on SRAM circuits have been analyzed in terms of independent multi-Poisson processes describing the occurrence of single events as a function of bit flip multiplicity. Applied for both neutron-induced and alpha particle-induced SERs, this detailed analysis highlights the respective contributions of atmospheric radiation and alpha contamination to multiple cell upset mechanisms. It also offers a simple way to predict by simulation the radiation response of a given technology for any terrestrial position, as illustrated here for bulk 65 nm and 40 nm SRAMs. Highlights: The occurrence of soft errors during real-time tests has been analyzed. Single events have been considered as a function of bit flip multiplicity. Multiple cell upsets have been described as independent multi-Poisson processes. Neutron and alpha contributions have been extracted for each event multiplicity. The method is illustrated for bulk 65 nm and 40 nm SRAMs.